A New Data-Based Motor Subtype Schema for Delirium - Meagher, David; Moran, Maria; Raju, Bangaru; Leonard, Maeve; Donnelly, Sinead; Saunders, Jean; Trzepacz, Paula (The journal of neuropsychiatry and clinical neurosciences, 2008)
The authors sought to validate a new approach to motor subtyping in delirium based on data from a controlled comparison of items from three existing psychomotor schema combined into the Delirium Motoric Checklist. Principal components analysis of the Delirium Motoric Checklist identified two factors that correlated significantly with independently assessed motor agitation and retardation. Symptoms loading at >0.65 were extracted to form subtype criteria composed of four hyperactive items and seven hypoactive items which, when applied to the delirious population, suggested a cutoff of two items for subtypes. This new scale is derived from existing approaches but is more concise, focused on motor disturbances, and validated against nondelirious comparison subjects and independently rated motor disturbance.